Protein Kinase WNK2 has a Tumour Suppressor Role in Gliomas - Moniz, Sonia (2012)
Malignant glioblastoma is the most common and lethal adult brain tumour type. Recently, the promoter region of the protein kinaseWNK2 gene was found to be hypermethylated in 29 of 31 infiltrative gliomas and about 5 of 7 meningiomas. We have previously described that theexperimental depletion of WNK2 expression decreases RhoA activity whilst leading to increased Rac1 activity. RhoA/Rac1 activities are important forcell migration and glioblastomas are very invasive tumours so that we tested the effects of WNK2 on wound-healing assays in glioma cell lines SW1088and A172. SW1088 cells express endogenous WNK2 and we observed that wound closure was increased upon experimental depletion of endogenousWNK2. In contrast, A172 cells display complete promoter region methylation and WNK2 re-expression was found to decrease migration. Consistently,we observed an increase in Rac1 activity in SW1088 cells upon WNK2 down-regulation, but lower levels of active Rac1 in A172 cells stably expressingWNK2 cDNA when compared with an equivalent cell line stably transfected with the same empty vector. Our studies indicate that loss of WNK2expression promotes Rac1 activation and may contribute to the highly invasive phenotype that glioblastomas present.